Data Access for Research: A New Era in Online Integrity - McNally, Naoise (Statistical and Social Inquiry Society of Ireland, 2025)
The rapid proliferation of online harms over the past fifteen years has exposed fundamental flaws in platform self-regulation, with information asymmetries preventing independent researchers from accessing data necessary to understand and address digital risks. Article 40 of the European Union's Digital Services Act represents a paradigm shift, establishing the first global mandate for research data access on social media platforms and search engines. This paper examines Article 40's implementation framework, analysing its regulatory structure, scope, and implications for evidence-based digital governance. The analysis reveals how Article 40 addresses longstanding information asymmetries through a two-tier data access system, enabling unprecedented research opportunities while establishing safeguards for privacy and platform concerns. The framework's focus on systemic risks – including illegal content dissemination, fundamental rights violations, and threats to democratic processes – ensures regulatory alignment while constraining research scope. However, successful implementation faces significant challenges, including substantial administrative burdens on regulators, institutional capacity requirements, and platform resistance to data transparency. With Ireland's Coimisiún na Meán serving as coordinator for 15 of 25 designated platforms, the framework's global implications extend beyond European borders. Article 40’s success will ultimately depend on navigating complex implementation challenges to deliver the rigorous, systematic investigation that contemporary digital governance demands.
read before the Society, 30th April 2025 - Symposium: Big Tech and Big Data - New Frontiers in Regulation
Keywords: digital governance and regulation; digital services; research data; ethical data use; 314.15